2022
DOI: 10.1589/jpts.34.306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interferential current on deep abdominal muscle thickness

Abstract: We aimed to investigate the effects of various modulated interferential currents on deep abdominal muscle thicknesses of healthy participants using ultrasound imaging. [Participants and Methods] We recruited twenty-two healthy male participants for this study. We compared the rate of change in muscle thickness of the abdominal muscles under different stimulation interferential current conditions. [Results] The change in interclass correlation coefficient of muscle thickness for each electrical stimulation by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Since the discovery of electricity, it has been known that electricity stimulates nerve fibers and induce muscle contractions during physiotherapy, and low and medium waveforms can be produced by varying the frequency of the electrical current. The effect of electrical stimulation on muscles enhances local metabolism, increases neuromuscular excitability and motor neurons, promotes the growth and germination of axons and neuromuscular junction regeneration [ 59 ], thus repairs and rebuilds the damaged or atrophied denervated skeletal muscles, and improves muscle quality and strength [ 15 , 60 62 ]. Blickenstorfer and Kampe reported that the application of electrical stimulation to some skeletal muscles could induce brain plasticity of the pain-associated sensorimotor cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of electricity, it has been known that electricity stimulates nerve fibers and induce muscle contractions during physiotherapy, and low and medium waveforms can be produced by varying the frequency of the electrical current. The effect of electrical stimulation on muscles enhances local metabolism, increases neuromuscular excitability and motor neurons, promotes the growth and germination of axons and neuromuscular junction regeneration [ 59 ], thus repairs and rebuilds the damaged or atrophied denervated skeletal muscles, and improves muscle quality and strength [ 15 , 60 62 ]. Blickenstorfer and Kampe reported that the application of electrical stimulation to some skeletal muscles could induce brain plasticity of the pain-associated sensorimotor cortex.…”
Section: Discussionmentioning
confidence: 99%